Molecular transport machinery involved in orchestrating luminal acid‐induced duodenal bicarbonate secretion in vivo. (18th October 2013) - Singh, Anurag Kumar; Liu, Yongjian; Riederer, Brigitte; Engelhardt, Regina; Thakur, Basant Kumar; Soleimani, Manoocher; Seidler, Ursula
Key points: Acid damage of the proximal duodenum is a key pathogenic factor in duodenal ulcer disease as well as in the intestinal manifestations of cystic fibrosis. Short contact of healthy duodenal mucosa with acid results in long‐lasting stimulation of proximal duodenal bicarbonate secretion. While the complex neural, paracrine, humoral and luminocrine regulation of this acid‐induced bicarbonate secretory response, as well as its protective role, has been studied in some detail, little is known about the molecular identity of the involved ion transporters or intracellular signalling. Using genetically engineered mouse models, we found that the anion exchanger DRA (Slc26a3), the anion conductances Slc26a9 and cystic fibrosis transmembrane conductance regulator, and the Na + /H + exchanger isoform 3 play essential roles in orchestrating the acid‐induced duodenal bicarbonate secretory response. These transporters are differentially controlled by signalling mechanisms along the crypt–villus axis. These findings provide a better understanding of the pathophysiology of peptic damage to the duodenum and may provide novel treatment strategies. Abstract The duodenal villus brush border membrane expresses several ion transporters and/or channels, including the solute carrier 26 anion transporters Slc26a3 (DRA) and Slc26a6 (PAT‐1), the Na + /H + exchanger isoform 3 (NHE3), as well as the anion channels cystic fibrosis transmembrane conductance regulator (CFTR) and Slc26a9. Using genetically engineered mouse models lacking Scl26a3, Slc26a6, Slc26a9 or Slc9a3 (NHE3), the study was carried out to assess the role of these transporters in mediating the protective duodenal bicarbonate secretory response (DBS‐R) to luminal acid; and to compare it to their role in DBS‐R elicited by the adenylyl cyclase agonist forskolin. While basal DBS was reduced in the absence of any of the three Slc26 isoforms, the DBS‐R to forskolin was not altered. In contrast, the DBS‐R to a 5 min exposure to luminal acid (pH 2.5) was strongly reduced in the absence of Slc26a3 or Slc26a9, but not Slc26a6. CFTR inhibitor [CFTR(Inh)‐172] reduced the first phase of the acid‐induced DBS‐R, while NHE3 inhibition (or knockout) abolished the sustained phase of the DBS‐R. Luminal acid exposure resulted in the activation of multiple intracellular signalling pathways, including SPAK, AKT and p38 phosphorylation. It induced a biphasic trafficking of NHE3, first rapidly into the brush border membrane, followed by endocytosis in the later stage. We conclude that the long‐lasting DBS‐R to luminal acid exposure activates multiple duodenocyte signalling pathways and involves changes in trafficking and/or activity of CFTR, Slc26 isoforms Slc26a3 and Slc26a9, and NHE3.